Premature termination of fixed-term contract and its remedies - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
The engagement of workers on fixed-term contracts must be based on genuine grounds. A genuine fixed-term contract will terminate automatically on the date specified therein. In such cases, the issue whether the worker was dismissed from employment does not arise. In view of the above, this chapter discusses the prerogative of the employer to engage workers on a fixed-term basis and the workers legitimate expectation for an automatic renewal of their contract. Reference will also be made to hiring of migrant workers on fixed-term contracts and the remedies in the event the contract is prematurely determined.